2022
DOI: 10.1186/s12916-022-02496-w
|View full text |Cite
|
Sign up to set email alerts
|

Diet and irritable bowel syndrome: an update from a UK consensus meeting

Abstract: There has been a renewed interest in the role of dietary therapies to manage irritable bowel syndrome (IBS), with diet high on the agenda for patients. Currently, interest has focussed on the use of traditional dietary advice (TDA), a gluten-free diet (GFD) and the low FODMAP diet (LFD). A consensus meeting was held to assess the role of these dietary therapies in IBS, in Sheffield, United Kingdom.Evidence for TDA is from case control studies and clinical experience. Randomised controlled trials (RCT) have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 81 publications
(128 reference statements)
0
8
0
Order By: Relevance
“…In adults, differing FODMAP content has been tested depending on the diet used; allowed amounts have been 7.6 g/day, 15.2 g/day, and 22.4 g/day for a low-FODMAP diet, traditional dietary advice, and GFD, respectively. A suggested threshold for symptom improvements in adults is 12 g FODMAPs/day [ 29 ]. However, this has yet to be confirmed in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, differing FODMAP content has been tested depending on the diet used; allowed amounts have been 7.6 g/day, 15.2 g/day, and 22.4 g/day for a low-FODMAP diet, traditional dietary advice, and GFD, respectively. A suggested threshold for symptom improvements in adults is 12 g FODMAPs/day [ 29 ]. However, this has yet to be confirmed in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, there has been renewed interest in the role of specific dietary patterns in the treatment of FGIDs. Currently, interest is focused on the low-FODMAP diet [ 27 ], fructose- or lactose-restricted diet (FRD or LRD) [ 28 ], gluten-free diet (GFD) [ 29 ], and Mediterranean diet (MD) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adapted from Rej et al [93]. GFD, gluten-free diet; mNICE, National Institute for Health and Care Excellence; LFD, low-FODMAP diet; TDA, traditional dietary advice.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high content of fructans (0.7–2.9 g% in wheat flour), wheat is one of the major sources of dietary FODMAPs, a group of poorly absorbed carbohydrates that increase small bowel water content by osmosis and release gases, predominantly carbon dioxide and hydrogen, from bacterial fermentation. Over the last decade, there has been considerable interest in the role of the low FODMAP diet (LFD) to manage patients with IBS, a functional intestinal disorder largely overlapping with NCWS [ 8 ]. A recent systematic review on the effectiveness of the LFD in improving NCWS concluded that the GFD represent first-line therapy but also that a complete FODMAP restriction (not only wheat fructans) can further decrease gastrointestinal symptoms in individuals with NCWS [ 9 ].…”
Section: What Is the Trigger Of Nonceliac Wheat Sensitivity?mentioning
confidence: 99%
“…As previously noted, there is overlap between the LFD and the GFD, in that the GFD eliminates wheat derivatives that are also the major source of FODMAPs (fructans), and IBS patients often self-initiated gluten/wheat reduction as part of their LFD. To avoid this confusing situation and optimize dietary treatment, a recent UK Consensus document recommends that (a) dietary therapies for IBS should be offered by dietitians (instead than physicians/gastroenterologists) who first assess dietary triggers and then tailor the intervention according to patient choice; (b) novel approaches such as employing group clinics and online webinars may maximize capacity and accessibility for patients [ 8 ]. Further research is required to assess the comparative efficacy of dietary therapies to other management strategies available to manage IBS.…”
Section: Dietary Treatment Of Nonceliac Wheat Sensitivity-related Irr...mentioning
confidence: 99%